Polymorphism of Uncoupling Protein 2 (UCP2) Gene in Obes People with the Family History of Type 2 Diabetes Mellitus - Setyawati, Tri (Walailak University, 2022)
History with type 2 diabetes mellitus (T2DM) is manifested by the presence of insulin resistance and β-cell dysfunction which prerequisites for T2DM development involving unbalanced energy intake and expenditure. Uncoupling gene protein 2 is the main regulator of energy balance. This study aims to determine the UCP2-866G/A genetic variation in obese individuals with a family history of T2DM and without a family history of T2DM. The study was a case control design in which the case subjects (n = 60) were obese individuals with a family history of T2DM and control subjects (n = 60) without a family history of T2DM. Polymorphism was analyzed with PCR-RFLP. The value of HOMA-IR and HOMA-β was calculated by the HOMA formula. Data was analyzed by Independent Sample t-test, Mann Whitney U-test, Chi-Square test and Kruskal-Wallis test with a significance level of p < 0.05. The frequency of genotype and alleles in obese individuals with a family history of T2DM and without a history of T2DM did not differ significantly, GA+AA (56.7 ) and A (32.5 ) allele was higher in individuals with a family history of T2DM. The GG+AA genotype in the male group with a family history of T2DM could significantly increase the risk of UCP2 gene polymorphism in T2DM by 2.23 times (CI 95 0.64-8.14) whereas in the female group there was no risk of T2DM. HOMA-IR and HOMA-β value in both family background did not differ significantly. The value of HOMA-β in the female gender group had significant relationship between obese individuals with a family history of T2DM (p = 0.04). Conclusion: The result suggests obese individuals with a family history of T2DM have a higher risk of getting GA+AA genotypes and A allele than individuals without a family history of T2DM. © 2022, Walailak University. All rights reserved.